Methylmercury exposure alters RNA splicing in human neuroblastoma SK-N-SH cells: Implications from proteomic and post-transcriptional responses. (July 2018) - Li, Yiling; He, Bin; Gao, Jiejun; Liu, Qian S.; Liu, Runzeng; Qu, Guangbo; Shi, Jianbo; Hu, Ligang; Jiang, Guibin
Abstract: The neurotoxic effects of methylmercury (MeHg) have been intensively studied. However, the molecular mechanisms responsible for the neurotoxicity of MeHg are not fully understood. To decipher these mechanisms, proteomic and high-throughput mRNA sequencing (RNA-seq) technique were utilized, comprehensively evaluating the cellular responses of human neuroblastoma SK-N-SH cells to MeHg exposure. Proteomic results revealed that MeHg exposure interfered with RNA splicing via splicesome, along with the known molecular mechanisms of mercury-related neurotoxicity (e.g. oxidative stress, protein folding, immune system processes, and cytoskeletal organization). The effects of MeHg on RNA splicing were further verified using RNA-seq. Compared to control, a total of 658 aberrant RNA alternative splicing (AS) events were observed after MeHg exposure. Proteomics and RNA-seq results also demonstrated that mercury chloride (HgCl2 ) influenced the expression levels of several RNA splicing related proteins and 676 AS events compared to control. These results suggested that RNA splicing could be a new molecular mechanism involved in MeHg and HgCl2 neurotoxicity. Graphical abstract: Image 1 Highlights: RNA splicing was a novel identified pathway involved in MeHg neurotoxicity. Both proteomic and RNA-seq revealed that MeHg interfered with RNA splicing. All the five types of alternative splicing were influenced by MeHg exposure. HgCl2 altered RNA splicing in a similar way to MeHg. Abstract : This study demonstrated that post-transcriptional RNA splicing involved in MeHg toxicity to SK-N-SH cells based on both proteomic and RNA-seq results.